2018
DOI: 10.5539/mas.v12n12p217
|View full text |Cite
|
Sign up to set email alerts
|

Students Attitudes toward Blended Learning among students of the University of Jordan

Abstract: Information and communication Technology and the use of internet has added many values to the educational process. Many approaches has been developed for this purpose including e-learning, distant learning and recently blended learning. Many universities are adopting these approaches for teaching students. Therefore this research aims to examine attitudes of University of Jordan students toward blended learning. A sample of 250 students were selected to complete online questionnaire who have taken blended cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
5
12
0
Order By: Relevance
“…Therefore, it should be included in the inputs of university education institutions in alignment with the requirements of the current situation and within the framework of the philosophy of higher education. (6:16) These results agree with the study of "Fatima Aladwan" (2018) (20), "Ibrahim Abdullah" (2021) (1), "Shaimaa Mustafa, Safinaz Muhammad" (2021) (7), "Essa Muhammad" (2021) (11) in creating a positive attitude towards Hybrid Learning, as it is a method that facilitates the learning process under Covid-19. The electronic resources provided through Hybrid Learning are an effective way to help students acquire knowledge and improve their skills, and have a tremendous impact on students taking responsibility for their own learning process.…”
Section: Third: Review and Discussion Of Theme Three Resultssupporting
confidence: 82%
“…Therefore, it should be included in the inputs of university education institutions in alignment with the requirements of the current situation and within the framework of the philosophy of higher education. (6:16) These results agree with the study of "Fatima Aladwan" (2018) (20), "Ibrahim Abdullah" (2021) (1), "Shaimaa Mustafa, Safinaz Muhammad" (2021) (7), "Essa Muhammad" (2021) (11) in creating a positive attitude towards Hybrid Learning, as it is a method that facilitates the learning process under Covid-19. The electronic resources provided through Hybrid Learning are an effective way to help students acquire knowledge and improve their skills, and have a tremendous impact on students taking responsibility for their own learning process.…”
Section: Third: Review and Discussion Of Theme Three Resultssupporting
confidence: 82%
“…Typically, some teachers mentioned that the unstable internet connection hampered their conduct of online classes; hence, they resorted to a synchronous approach. This finding echoes previous studies which revealed that blended learning greatly relies on internet connectivity (Aladwan et al, 2018); the availability of internet infrastructure (Fitri & Zahari, 2019); the presence of technology (Kocour, 2019); and technical and equipment (Rao, 2019). It implies that the location where the teachers and students are located lacks advanced technology and equipment.…”
Section: Complication On Flexible Learningsupporting
confidence: 86%
“…Tashiro and Hebeler (2019) mentioned that many of the learners at home are not ready for blended learning due to the lack of support. Likewise, blended learning is greatly dependent on internet connection and time (Aladwan et al, 2018); infrastructure (Fitri & Zahari, 2019); technology (Kocour, 2019); technical resources and equipment (Rao, 2019); and self-regulation of using technology (Rasheed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the fact that Blended Learning utilization affects positively attitudes of learners, it can also develop and enhance their knowledge and skills. For instance, the electronic resources provided through blended learning represent a tremendous effect on increasing students' responsibility for their own learning process making it clearer (Aladwanm, Fakhouri, Alawamrah, & Rababah, 2018). Studies also show that students prefer Blended Learning as a teaching approach though they think that paper-and-pencil exams are more comfortable.…”
Section: Evaluation Of Blended Learningmentioning
confidence: 99%